Drug-Resistant Temporal Lobe Epilepsy Alters the Expression and Functional Coupling to Gαi/o Proteins of CB1 and CB2 Receptors in the Microvasculature of the Human Brain - Nuñez-Lumbreras, María de los Ángeles; Castañeda-Cabral, José Luis; Valle-Dorado, María Guadalupe; Sánchez-Valle, Vicente; Orozco-Suárez, Sandra; Guevara-Guzmán, Rosalinda; Martínez-Juárez, Iris; Alonso-Vanegas, Mario; Walter, Fruzsina; Deli, Maria A.; Carmona-Cruz, Francia; Rocha, Luisa (Frontiers in Behavioral Neuroscience, 2021)
Cannabinoid receptors 1 and 2 (CB1 and CB2, respectively) play an important role in maintaining the integrity of the blood-brain barrier (BBB). On the other hand, BBB dysfunction is a common feature in drug-resistant epilepsy. The focus of the present study was to characterize protein expression levels and Gαi/o protein-induced activation by CB1 and CB2 receptors in the microvascular endothelial cells (MEC) isolated from the brain of patients with drug-resistant mesial temporal lobe epilepsy (DR-MTLE). MEC were isolated from the hippocampus and temporal neocortex of 12 patients with DR-MTLE and 12 non-epileptic autopsies. Immunofluorescence experiments were carried out to determine the localization of CB1 and CB2 receptors in the different cell elements of MEC. Protein expression levels of CB1 and CB2 receptors were determined by western blot experiments. [35S]-GTPγS binding assay was used to evaluate the Gαi/o protein activation induced by specific agonists. Immunofluorescent double-labeling showed that CB1 and CB2 receptors colocalize with tight junction proteins (claudin-5, occludin and zonula occludens-1), GFAP and PDGFR-β. These results support that CB1 and CB2 receptors are expressed in the human isolated microvessels fragments consisting of MEC, astrocyte end feet and pericytes. The hippocampal microvasculature of patients with DR-MTLE presented lower protein expression of CB1 and CB2 receptors (66% and 43%, respectively; p<0.001). However, its Gαi/o protein activation was with high efficiency (CB1, 251%, p<0.0008; CB2, 255%, p<0.0001). Microvasculature of temporal neocortex presented protein overexpression of CB1 and CB2 receptors (35% and 41%, respectively; p<0.01). Their coupled Gαi/o protein activation was with higher efficiency for CB1 receptors (103%, p<0.006), but lower potency (p<0.004) for CB2 receptors. The present study revealed opposite changes in the protein expression of CB1 and CB2 receptors when hippocampus (diminished expression of CB1 and CB2) and temporal neocortex (increased expression of CB1 and CB2) were compared. However, the exposure to specific CB1 and CB2 agonists results in high efficiency for activation of coupled Gαi/o proteins in the brain microvasculature of patients with DR-MTLE. CB1 and CB2 receptors with high efficiency could represent a therapeutic target to maintain the integrity of the BBB in patients with DR-MTLE.